Number 2 (August 1976) - M. F. Mettee (Southeastern Fishes Council Proceedings, 1976)
A Status Report on the Okaloosa Darter in Northwest Florida. By M.F. Mettee, et al., plus NewsNotes, 4pp.
Keywords: fishes; Okaloosa Darter